The efficacy of intra-arterial lignocaine as an adjuvant analgesic in the management of post-procedural pain following uterineartery embolization for symptomatic uterine fibroids – a comparative study of outcomes - Human, Gercois Paul (Division of Radiology, 2022)
Background: Uterine artery embolisation (UAE) for symptomatic fibroids has been shown to be an effective and beneficial procedure in our South African population, especially considering any cultural stigma related to hysterectomy. Post procedural pain following UAE can be very significant. Regular review of pain management protocols in our population is therefore warranted. In particular, the benefit of intra-arterial lignocaine as an adjunctive analgesic following UAE remains uncertain. Method: A single institution retrospective comparative study was undertaken through review of folders of patients who were treated for symptomatic uterine fibroids by UAE between July 2016 and November 2019. Two groups were compared – those who underwent UAE without the use of intraarterial lignocaine (Control group) and those who received intra-arterial lignocaine (Study group). Baseline characteristics and periprocedural outcomes were compared together with an 11-Point pain scale which was recorded during the post procedural rounds at the end of the day. Results: A total of 473 patients were included in the study, with 142 patients in the Control group and 331 patients in the study group. No significant differences were found in the 11-point pain scores between the two groups (p=0.34). However, additional medication usage was slightly higher in the Control group (p=0.05), together with longer hospital stay (p <0.01) and felt markedly less constipated on day 2 (p<0.01). Conclusion: Despite no significant overall pain score reduction, intra-arterial lignocaine after UAE for uterine fibroids correlated with reduced additional medication use, shorter hospital stays and less feeling of nausea and constipation.